The Exploring emotional factors behind brand loyalty among taxi users in Jakarta - Boer, Rino Febrianno; Nurfitriandra, Utari (Faculty of Communications Science, Dr. Soetomo University, 2025)
study explored how Bluebird, a leading legacy taxi brand in Indonesia, sustains customer loyalty amidst the rise of digital ride-hailing services. Facing digital disruption, Bluebird’s strategy of blending tradition with innovation provides valuable insights into how established brands can adapt to a rapidly evolving market. a combination of statistical modelling and path analysis grounded in Katz’s Uses and Gratifications Theory, the study distributed structured questionnaires to 251 purposively selected respondents specifically individuals who has used Bluebird taxi services at least three times in the past three months in Jakarta to capture constructs such as sensory and affective experience, emotional attachment, brand satisfaction, and brand love. Statistical modelling via SmartPLS 3.0 and path analysis revealed that while brand experience significantly influences brand loyalty, brand satisfaction does not have a direct effect. Instead, emotional attachment and love mediate this relationship, with through the indicator of sustain commitment, where respondents showed a strong sense of belonging to the brand. These findings highlight that in a highly competitive urban mobility market, functional satisfaction is no longer sufficient; emotional connection is key. Practical strategies such as loyalty programs, driven marketing, and brand storytelling are recommended to enhance customer retention.